Basic Motion Learning Model Locomotor Based On The Iv Elementary School Student Play Approach - Purba, Yan Sumitro; Subandi, Oman Unju; Samsudin, Samsudin; Sujarwo, Sujarwo (JUPE : Jurnal Pendidikan Mandala, 2025)
This research exists or appears for education that is developing significantly. Especially in the field of physical education, this research offers learning based on the play approach to its application. The existing benefits certainly provide students with new experiences in the learning process of the basic motion of locomotor in schools. Where the renewable play approach becomes something interesting for students. Research and development used using the Addie method, including analysis, design, develop, implementation, and evaluation. This study involved as many as 119 elementary school students in grade IV. According to the age of the play approach it was very suitable to be applied. Evidenced by the acquisition of each data analysis in the trial at each stage. The small trial got 80.6% while the large trial got 80.72%. In addition, the N Gain test received a percentage of 48.9%, where this result was a good data result for the model development category. From the effectiveness test this model can be applied by the teacher in grade IV elementary school students. Keywords: physical education, locomotor motion, walking, running, jumping